PP.51 Perinatal Outcomes in Twin Pregnancy in Ireland. (26th April 2013) - Mahony, AM O'; Meaney, S; Donoghue, K O'
Abstract : Introduction: Over the past two decades multiple births have been increasing in Ireland, in 2011 17.9 sets of twins per 1, 000 live births were born. This study aims to investigate adverse perinatal outcomes in twin pregnancies. Methods: A retrospective cohort study of all twin pregnancies delivered from 2009 to 2011 in a large, tertiary hospital (∼8, 000 deliveries per annum) in the Republic of Ireland was conducted. Birth registers, NCIU and clinic records were reviewed to examine perinatal outcomes. Results: Of the 523 twin pregnancies included in the study mean gestational age at delivery was 35.1 ± 3.8 (weeks). 79.1% (n = 413) delivered preterm (<37 weeks) of which 75.8% (n = 313) were classified as late preterm infants, delivering between 34–37 weeks. Among the 523 twins 47.5% (n = 247) were nulliparous and 16.3% (n = 87) were monochorionic (MC). Nulliparity and MC were both significantly associated with preterm delivery (p = 0.02 and p < 0.001, respectively). Both had lower mean gestational ages (p = 0.007 and p < 0.001, respectively) with significant lower birth weights (p < 0.001) compared to parous and dichorionic (DC) pregnancies. Intra-uterine fetal death (11.9% vs. 1.3%; p < 0.001), TTTS (24.1% vs. 0.1%; p < 0.001) and perinatal mortality (p = 0.002) were higher in MC pregnancies compared to DC. Mean maternal age was 33.2 ± 4.9 years and fetal anomalies increased with advanced maternal age; <40 years of age, (p = 0.01). Conclusion: Our findings show that monochorionicity and nulliparity are associated with adverse perinatal outcomes in twin pregnancies, and confirm that these pregnancies warrant close antenatal surveillance.